Pengembangan Biological Macromolecules Three-Tier Test (BM-3T) untuk Mengidentifikasi Miskonsepsi Calon Guru IPA - Ni Wayan Suriani; Brian Ricard Wola; Alfrits Komansilan (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop a valid and reliable biological macromolecules three-tier test (BM-3T) so that it is feasible to identify misconceptions of prospective science teachers. This research is a type of research and development by following the research design by KiliÃ§ and SaÄŸlam, which consists of three stages, namely defining content, obtaining information on student misconceptions, and developing tests. Research data was obtained through interviews, validation, and test trials. The subjects in this study consisted of 14 prospective science teachers in the first semester in the 2021/2022 academic year at the Universitas Negeri Manado. The data analysis carried out includes the analysis of test validity, test reliability analysis, and test difficulty level analysis. The results showed that the 16 test items developed were declared valid, the test reliability coefficient of 0.78 was in the reliable category, and the level of difficulty of BM-3T shows an average value of 0.44, which is included in the moderate category. Therefore, BM-3T is appropriate to identify misconceptions of prospective science teachers on the topic of biological macromolecules.